2006
DOI: 10.1016/j.jebo.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Poverty in dictator games: Awakening solidarity

Abstract: This paper investigates the effect of poverty and good intentions on dictator game giving. Previous experimental studies in which information was supplied to dictators about recipients have shown that dictator giving increases overall in this context. We develop a new design of standard informed dictator games with three main variants: 1) three recipients are used instead of one; 2) dictators are informed that their recipients are poor; 3) dictators give donations in the form of medicines instead of money. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 16 publications
(23 reference statements)
6
94
0
5
Order By: Relevance
“…From a micro perspective, Fosco and Mengel (2008) set up an evolutionary model by which, in the steady state, prosocial and sel…sh individuals coexist, with the latter located "at the periphery" of the network. 6 The main objective of this paper is precisely to test the conjecture that more socially integrated individuals exhibit, on average, more altruistic behavior. To this aim, we relate the altruistic attitudes of an undergraduate section of Economics students of the Universidad de Granada to their real-life social-network position in a two-stage experiment in which i) we …rst ask subjects to elicit the underlying social network of their section and then ii) obtain an indirect measure of their altruism by means of a standard Dictator Game.…”
Section: Motivationmentioning
confidence: 99%
“…From a micro perspective, Fosco and Mengel (2008) set up an evolutionary model by which, in the steady state, prosocial and sel…sh individuals coexist, with the latter located "at the periphery" of the network. 6 The main objective of this paper is precisely to test the conjecture that more socially integrated individuals exhibit, on average, more altruistic behavior. To this aim, we relate the altruistic attitudes of an undergraduate section of Economics students of the Universidad de Granada to their real-life social-network position in a two-stage experiment in which i) we …rst ask subjects to elicit the underlying social network of their section and then ii) obtain an indirect measure of their altruism by means of a standard Dictator Game.…”
Section: Motivationmentioning
confidence: 99%
“…This means that part of the altruism in the DG is to avoid being labeled as too selfish, to look good or not to look bad. Similarly, the experiment by BraĔas-Garza (2006) cited earlier, which introduces poverty in the DG, concludes that informing the dictator about the poverty of the recipient leads to more altruism. Again, this is because information about the socio-economic status of players leads to changes in relative states and equity-biases, which leads to different outcomes.…”
Section: Application Of the Modementioning
confidence: 78%
“…Eckel and Grossman, (1996) found a significant increase in donations in a dictator game when they increased the extent to which a donation goes to a "deserving" recipient. BraĔas-Garza (2006) performed three different dictator games; the standard DG and two versions of the DG with poverty where the dictator is informed that their recipients were poor. Garza found that giving in the poverty game was significantly higher than in the standard DG.…”
Section: The Psychological Test (P-test)mentioning
confidence: 99%
“… "earned" right to become the dictator (Hoffman et al 1994)  double and single blind procedures (Hoffman et al 1996)  silent identification and face-to-face communication (Bohnet and Frey 1999)  complete double blind procedure (Johannesson and Persson 2000)  picture viewing procedure (Burnham 2003)  poverty and medicine instead of money (Brañas-Garza 2006)  degree of anonymity and gender (Dufwenberg and Muren 2006)  opportunity to make a request (Rankin 2006)  family name of recipient (Charness and Gneezy 2008)  request and communication effects (Yamamori et al 2008)  gender and expectations (Aguiar et al 2009)  directed altruism and future interaction (Leider et al 2009)  friendship networks (Goeree et al 2010)  social integration (Brañas-Garza et al 2010) Note that although inequality aversion and social discounting are both social preferences, they are clearly differentiated. The results of dictator games indicate that D offers a certain share even to a stranger.…”
Section: Introductionmentioning
confidence: 99%